Child and Youth Participation in Policy, Practice and Research - Horgan, Deirdre; Kennan, Danielle (Taylor & Francis, 2021)
This book showcases rights based participatory approaches to policy-making, practice and research with children and youth. Throughout its three parts, the book conceptualises a rights-based participatory approach; showcases constructive and innovative rights based participatory approaches across the domains of research, policy and practice; and interrogates the challenges and complexities in the implementation of such an approach. In recent times, Ireland has been at the forefront of promoting and implementing participatory approaches to policy-making, practice and research focused on children and youth. This edited volume is a timely opportunity to capture previously undocumented learning generated from a wide range of innovative participatory initiatives implemented in Ireland. In capturing this learning, real world guidance will be provided to international policy-makers, practitioners and researchers working with children and youth. This book is essential reading for those interested in a rights based participatory approach, for those who want to appropriately and meaningfully engage children and youth in research, and for those wishing to maximise the contribution of children and youth in policy-making.